Physical Needs of Language Resource Centre to Support English Language Learning - Budiyanti, Kurnia; Juita, Novia; Ardi, Havid; Wati, Siska Oktawidya (Journal of English Language and Education, 2024)
A learning resource centre must have facilities that can be used by students in seeking information and knowledge. The present study aimed to investigate the students’ perception of the physical needs of resource centre to support English language learning. The study employed qualitative approach with a case study design. The participants of the research were 104 English Department students. Questionnaire and interview were used to collect the data. The results showed that there was a neutral indication on students’ perception of the physical needs of the LRC. The language resource centre facilitated the students to find out some references for course assignments, to obtain addition information on certain subject, to enrich students’ knowledge through book review program, and to build independent learning through digitalization. However, the availability of up-to-date materials collection, EFL website access, and sustainable language program should be developed and qualified. Therefore, a constructive solution is needed to optimize the functions of learning resource centre to support English language learning.